IMPACT OF THE ANTIVIRAL THERAPY ON CARDIAC HEMODYNAMICS IN PATIENTS WITH CHRONIC VIRAL HEPATITIS - M. V. Chistyakova; A. V. Govorin; E. V. Goncharova; E. V. Radaeva (Столичная издательская компания, 2015)
Aim. To study the effect of antiviral therapy (AVT) on some cardiac hemodynamic parameters in patients with chronic viral hepatitis (CVH).Material and methods. Segmental systolic and diastolic functions of the ventricles as well as global diastolic function were evaluated in 25 patients with CVH by pulsed tissue Doppler mapping and by the method of Doppler echocardiography, respectively. The blood flow speed and diameter of blood vessels in liver were determined by ultrasound Doppler. Cardiac hemodynamics was examined in all patients before and after AVT with interferon in combination with ribavirin with formation of persistent virological response. Healthy people (n=19) were included into control group.Results. Reduction in atrial and ventricular sizes, decrease in left ventricular mass, improvement of systolic function of both ventricles, as well as diastolic function of the left ventricle were found in patients with CVH after specific treatment. Reduction in hepatic arterial and portal blood flow speed and a total number of heart rhythm disorders were also observed. Therefore AVT in patients with CVH shows a positive impact on cardiac hemodynamics. Medium-strength correlation (r=0.31; p<0.05) was identified between Еm speed at fibrous ring of mitral valve and high viral load. Strong correlation (r=0.81; p<0.05) was also found between portal vein diameter and Sm speed at fibrous ring of tricuspid valve.Conclusion. Patients with CVH that do not receive AVT have worse prognosis and indicators of cardiac hemodynamics in comparison with patients who receive specific AVT.